A Case of Idiopathic Hypereosinophilic Syndrome Causing Mitral Valve Papillary Muscle Rupture. (12th November 2015) - Tamse, Tiffany; Rampersad, Avind; Jordan-Villegas, Alejandro; Ireland, Jill
Abstract : Idiopathic Hypereosinophilic Syndrome (IHES) is a rare disease that can be difficult to diagnose as the differential is broad. This disease can cause significant morbidity and mortality if left untreated. Our patient is a 17-year-old adolescent female who presented with nonspecific symptoms of abdominal pain and malaise. She was incidentally found to have hypereosinophilia of 16, 000 on complete blood count and nonspecific colitis and pulmonary edema on computed tomography. She went into cardiogenic shock due to papillary rupture of her mitral valve requiring extreme life support measures including intubation and extracorporal membrane oxygenation (ECMO) as well as mitral valve replacement. Pathology of the valve showed eosinophilic infiltration as the underlying etiology. The patient was diagnosed with IHES after the exclusion of infectious, rheumatologic, and oncologic causes. She was treated with steroids with improvement of her symptoms and scheduled for close follow-up. In general patients with IHES that have cardiac involvement have poorer prognoses.